2015
DOI: 10.4081/monaldi.2010.274
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s emotional reactions in cardiac rehabilitation: analysis and perspectives

Abstract: IntroduzioneParlare di Riabilitazione Cardiologica significa, in prima istanza, mettere il paziente in una posizione centrale ed attiva nel processo terapeutico. Per raggiungere questo scopo l'intervento riabilitativo deve essere il più possibile multidisciplinare in modo da poter intervenire su tutti i fattori biologici, psicologici e sociali.Dal momento stesso della nascita della Riabilitazione Cardiologica, la presa in carico delle problematiche psicologiche dei pazienti è diventato un vero e proprio outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…With regard to clinical distress, we detected a high prevalence of anxiety diagnoses (20.4%) and fewer cases of depressive disorders (12%). These data are partially in line with the literature showing a greater prevalence of anxiety, ranging from 27.8 per cent to 45 per cent (Serber, Todaro, Tilkemeier, & Niaura, 2009;Balestroni & Giannuzzi, 2010), and a similar frequency of clinical depression, ranging from 10 per cent to 20 per cent (Serber et al, 2009;Balestroni & Giannuzzi, 2010). Regarding subclinical psychological distress, we found that more than one-quarter of the sample reported baseline depressive and anxiety scores exceeding more than 1 standard deviation of the general population mean (Kellner, 1987), even in the absence of a formal psychiatric diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…With regard to clinical distress, we detected a high prevalence of anxiety diagnoses (20.4%) and fewer cases of depressive disorders (12%). These data are partially in line with the literature showing a greater prevalence of anxiety, ranging from 27.8 per cent to 45 per cent (Serber, Todaro, Tilkemeier, & Niaura, 2009;Balestroni & Giannuzzi, 2010), and a similar frequency of clinical depression, ranging from 10 per cent to 20 per cent (Serber et al, 2009;Balestroni & Giannuzzi, 2010). Regarding subclinical psychological distress, we found that more than one-quarter of the sample reported baseline depressive and anxiety scores exceeding more than 1 standard deviation of the general population mean (Kellner, 1987), even in the absence of a formal psychiatric diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…The CBA-H questionnaire also gives a score of Vital Exhaustion index (VE), composed of Interpersonal Difficulties (ID), and Perceived psychophysical Stress (PS) [ 10 , 20 ]. All CBA-H scores are in a negative direction (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The “Type A Personality” (TAP) predisposes to cardiovascular disorders, and characterizes individuals who are in a constant state of tension, hyperactive, and with a tendency to be hostile. The latter condition occurs when the subject has the feeling of not being able to have control, either of their own actions or on their social environment [ 10 ]. By contrast, “Type B” people are more relaxed and they adapt to their own experiences of stressful life with less tension and more acceptance, experiencing positive emotions.…”
Section: Introductionmentioning
confidence: 99%